Perception and Signaling of Strigolactones - Marzec, Marek (Frontiers in Plant Science, 2016)
Strigolactones (SLs), a recently discovered class of phytohormones, are important regulators of plant growth and development. While the biosynthetic pathway of these molecules is well documented, until recently there was not much known about the molecular mechanisms underlying SL perception and signal transduction in plants. Certain aspects of their perception and signalling, including the hormone-mediated interaction between receptor and F-box protein, degradation of suppressor proteins and activation of transcription factors, are also found in other phytohormones. However some of SL signalling features seem to be specific for the SL signalling pathway. These include the enzymatic activity of the SL receptor and its destabilisation caused by SLs. This review summarizes the current knowledge about SL signalling pathway in plants.